Combined NK-CIK and PD-1 inhibitor (nivolumab), an effective immunotherapy for treating intrahepatic lymphoepithelioma-like cholangiocarcinoma unassociated with EBV infection: Two case reports and a literature review - Sam Saji, Alen; Yang, Biao; Hou, Wan Ting; Liu, Xia; Ren, Qiu Ping; Wei, Yuan Feng; Zhang, Yu Zu; Yang, Xi (Frontiers in Oncology, 2023)
Intrahepatic lymphoepithelioma-like cholangiocarcinoma (LELCC) is a very rare malignant tumor arising from the biliary epithelium. Till now, the radiographical features, clinicopathological features, and treatment modalities of LELCC are in shortage of evidence as less than 28 cases of LELCC without EBV infection have been reported in the world. The treatment of LELCC still remains unexplored. Here, we present two cases of patients with LELCC without EBV infection, who were treated by liver resection, chemotherapy and immunotherapy who achieved long survival time. The patients received surgery to remove the tumors, then an adjuvant chemotherapy using GS regimen and combined immunotherapy using with NK-CIK and anti- PD-1/PDL-1 (Nivolumab) was performed. The patients achieved good prognosis and over 100 months and 85 months survival time, respectively.